(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The present study is a retrospective study conducted in Raichur institute of Medical sciences, Raichur Karnataka. During the study period that is from January 2017 to March 2017, out of 547 medico-legal cases which came to casualty, 164 cases were poisoning. Among 164 poisoning cases, 13 cases died in hospital and postmortem examination is done in mortuary RIMS Raichur hospital. The most common type of poisoning case in and around the Raichur district was organo-phosphorus poisoning (58.53%) followed by kerosene poisoning (13.41%). Males (55.48%) were the more common victims of the poisoning. Age group between 11-20 years (32.92%) was most commonly affected. Majority of poisoning cases was suicidal (84.14%) in manner. In 26.56% the motive for suicidal poisoning was financial crisis leading to depression and consumption of poisonous substance.